Labordiagnostik im Harn bei trächtigen Schafen und Jungschafen - Sendag, S.; Cetin, Y.; Failing, K.; Wehrend, A. (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2011)
Objective: The purpose of this study was to identify values for net acid base excretion (NABE) which are significant indicators of the acidbase equilibrium in pregnant and young ewes and to show its relationship with other parameters (base, acid, ammonium [NH4], base-acid quotient, sodium [Na], potassium [K], calcium [Ca]) in ovine urine. In contrast to dairy cows, data are rare on these parameters in ewes. Material and methods: A total of 99 animals were used in the study, consisting of 56 young (average of 5.6 ± 1.1 months) and 43 pregnant ewes (average of 35.2 ± 18.8 months). Measurement of fractional NABE in urine samples was carried out according to the method reported by Kutas. The pH value of the urine was measured with a laboratory pH meter. Na, K and total Ca were measured with a flame photometer. Results: For all values except Na significant differences occurred between urine samples of pregnant ewes and young ewes (p < 0.001). Base, acid, NH4, NABE, K and Ca values were significantly higher in the urine of the youngs than in pregnant ewes. In young ewes, a strong correlation was found between NABE and base values while a weak correlation could be observed between pH and base values. In pregnant ewes, strong NABE-base, NABE-K, K-acid and K-base correlations were found as well as weak NH4-base, NH4-NABE and NH4-K correlations. There was a strongly positive correlation between NABE and NH4 in pregnant ewes, while a weak negative correlation between those values was observed in young ewes. Conclusion: For the first time, we established values for NABE and certain other parameters in urine of pregnant ewes and young ewes. It was shown that the acid-base balance in pregnant ewes and young ewes can be evaluated by measuring NABE and certain trace elements in urine like in cattle.
Keywords: Net acid base excretion; urine; ewes